Proposed Levels of Christian Spiritual Maturity - Gibson, Timothy S. (Journal of psychology and theology, 2004)
Consideration is given to the ramifications of Lawrence Kohlberg's theory of moral reasoning for understanding Christian spiritual development. Utilizing Kohlberg's insights, four levels toward Christian spiritual maturity are identified: (a) accommodation to God's law, (b) respect for and obedience to God's law, (c) principle-centered commitment to a Christian worldview, and (d) Kingdom-centered commitment to God's glory. The discussion intends to challenge churches to foster an environment whereby people are more likely to reach a Postconventional level of spiritual maturity.